2015
DOI: 10.1051/0004-6361/201527094
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprints of giant planets in the photospheres of Herbig stars

Abstract: Around 2% of all A stars have photospheres depleted in refractory elements. This is hypothesised to arise from gas being accreted more efficiently than dust, but the specific processes and the origin of the material -circum-or interstellar -are not known. The same depletion is seen in 30% of young, disk-hosting Herbig Ae/Be stars. We investigate whether the chemical peculiarity originates in a circumstellar disk. Using a sample of systems for which both the stellar abundances and the protoplanetary disk struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
152
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(174 citation statements)
references
References 73 publications
21
152
0
Order By: Relevance
“…This is, together with the very low mass accretion rate, in line with the conclusions of Kama et al (2015), who propose that the depletion of heavy elements found in the stellar spectrum emerges as a Jupiter-like planet blocks the accretion of part of the dust and to lesser extent the gas.…”
Section: Large Grains and Free-free Emission Filling In The Disksupporting
confidence: 87%
“…This is, together with the very low mass accretion rate, in line with the conclusions of Kama et al (2015), who propose that the depletion of heavy elements found in the stellar spectrum emerges as a Jupiter-like planet blocks the accretion of part of the dust and to lesser extent the gas.…”
Section: Large Grains and Free-free Emission Filling In The Disksupporting
confidence: 87%
“…Second, early-type stars with metal-poor photospheres, in particular the λBoo stars, show an ultraviolet excess (Murphy & Paunzen 2017). Folsom et al (2012) and Kama et al (2015) found a relatively high fraction of HAeBes in their samples (up to ∼50%) showing the λBoo pattern to varying degrees. If this effect is common among the targets in our sample, it is possible that M  has been systematically overestimated.…”
Section: Appendix a Scattered-light Disk Samplementioning
confidence: 96%
“…The photospheric abundances of Herbig Ae/Be stars were recently shown to be a predictor of the inner disk gas and dust content (Kama et al 2015). This is in contrast to T Tauri stars, which have convective envelopes, where mixing rapidly erases accretion signatures.…”
Section: The Return Of Volatiles To the Gas In The Inner Diskmentioning
confidence: 99%